Sinibaldo de Más : a difusão da Ibéria em Portugal e do iberismo no oriente - Pereira, Maria da Conceição Meireles (2002)
In the mid 19th century the Spanish diplomat Sinibaldo de Más, after spending a period in the territory of Macao where he formulated his theories about the Iberian Peninsula, wrote a book which is considered to be a decisive contribution for the diffusion of the Iberian issue. This work that supported a peaceful union between Portugal and Spain under a common monarchy, was published five times in Spain and three times in Portugal. Latino Coelho and Carlos José Caldeira played an important role in the co-ordination of the Portuguese editions of the Ibéria, as well as in the organisation of other activities promoting the association of the two Iberian States, events in which Sinibaldo de Más was also involved.